Colonoscopy sedation: clinical trial comparing propofol and fentanyl with or without midazolam - Neves,Jose Francisco Nunes Pereira das (2016)
ABSTRACT Colonoscopy is one of the most common procedures. Sedation and analgesia decrease anxiety and discomfort and minimize risks. Therefore, patients prefer to be sedated when undergoing examination, although the best combination of drugs has not been determined. The combination of opioids and benzodiazepines is used to relieve the patient's pain and discomfort. More recently, propofol has assumed a prominent position. This randomized prospective study is unique in medical literature that specifically compared the use of propofol and fentanyl with or without midazolam for colonoscopy sedation performed by anesthesiologists. The aim of this study was to evaluate the side effects of sedation, discharge conditions, quality of sedation, and propofol consumption during colonoscopy, with or without midazolam as preanesthetic. The study involved 140 patients who underwent colonoscopy at the University Hospital of the Federal University of Juiz de Fora. Patients were divided into two groups: Group I received intravenous midazolam as preanesthetic 5 min before sedation, followed by fentanyl and propofol; Group II received intravenous anesthesia with fentanyl and propofol. Patients in Group II had a higher incidence of reaction (motor or verbal) to the colonoscope introduction, bradycardia, hypotension, and increased propofol consumption. Patient satisfaction was higher in Group I. According to the methodology used, the combination of midazolam, fentanyl, and propofol for colonoscopy sedation reduces propofol consumption and provides greater patient satisfaction.